Anticancer activities of Brachydin C in human prostate tumor cells (DU145) grown in 2D and 3D models: Stimulation of cell death and downregulation of metalloproteinases in spheroids - Oliveira, Larissa Cristina Bastos de; Ribeiro, Diego Luis; Nascimento, Jessyane Rodrigues do [UNESP]; Rocha, Claudia Quintino da; Cólus, Ilce Mara de Syllos; Serpeloni, Juliana Mara (Wiley, 2022)
Brachydin C (BrC) has demonstrated in vitro cytotoxic and antiproliferative effects in prostate cancer cells. In the present study, we compare the anticancer effects of BrC in DU145 cells grown in common bidimensional cultures (2D) and multicellular tumor spheroids (MCTS), often denominated 3D in vitro models, that can better mimic the microenvironment of tissues. BrC IC50 values obtained in the resazurin assay after 24 h of treatment were 47.31 μM (2D) and 229.8 μM (3D) and these cytotoxic effects were time-dependent only in 3D. BrC (5.0–60 μM) interfered with the growth of MCTS and reduced cell viability after 11 days of treatment, a result that is not attributable to oxidative stress evaluated using the CM-H2DCFDA probe. BrC (6.0 μM) impaired horizontal (wound-healing) and vertical cell migration and invasion (transwell assay) in 2D and BrC (5.0–60 μM) in 3D (ECM Gel®). BrC modulated the expression of genes BIRC5, TNF-α, CASP3, NKX3.1, MMP9, MMP11, CDH1, and ITGAM and downregulated proteins CASP7, BAX, and TNF-α in Western blotting analysis. In conclusion, BrC stimulated cell death and decreased epithelial–mesenchymal transition. Furthermore, DU145 MCTS displayed higher resistance to BrC-induced cell death than 2D cultures, a difference that should be considered in future approaches in prostatic cancer studies.
Keywords: chemotherapeutic; Fridericia platyphylla; metalloproteinases; phytochemical; survivin